Exploring Challenges to the Students and Faculty in an Undergraduate Integrated Dental Curriculum; A Qualitative Study. - Bushra Mehboob; Fatima Abdul Qaiyum; Brekhna Jamil; Tahira Amjad; Manahil Niazi; Neelofar Shaheen (Journal of Gandhara Medical and Dental Sciences)
OBJECTIVES